The antioxidant N-acetyl cysteine suppresses lidocaine-induced intracellular reactive oxygen species production and cell death in neuronal SH-SY5Y cells. Issue 1 (December 2016) - Okamoto, Akihisa; Tanaka, Masahiro; Sumi, Chisato; Oku, Kanako; Kusunoki, Munenori; Nishi, Kenichiro; Matsuo, Yoshiyuki; Takenaga, Keizo; Shingu, Koh; Hirota, Kiichi
Abstract Background The local anesthetic lidocaine can affect intra- and extra-cellular signaling pathways in both neuronal and non-neuronal cells, resulting in long-term modulation of biological functions, including cell growth and death. Indeed, lidocaine was shown to induce necrosis and apoptosis in vitro. While several studies have suggested that lidocaine-induced apoptosis is mitochondrial pathway-dependent, it remains unclear whether reactive oxygen species (ROS) are involved in this process and whether the observed cell death can be prevented by antioxidant treatment. Methods The effects of lidocaine and antioxidants on cell viability and death were evaluated using SH-SY5Y cells, HeLa cells, and HeLa cell derivatives. Cell viability was examined via MTS/PES ([3-(4, 5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium, inner salt]/phenazine ethosulfate) assay. Meanwhile, cell apoptosis and necrosis were evaluated using a cell death detection assay with Annexin V-FITC and PI staining, as well as by assaying for caspase-3/7 and caspase-9 activity, and by measuring the release of lactate dehydrogenase, respectively. Mitochondrial transmembrane potential (ΔΨm) was assessed using the fluorescent probe tetramethylrhodamine ethyl ester. Results Lidocaine treatment resulted in suppression of the mitochondrial electron transport chain and subsequent attenuation of mitochondrial membrane potential, as well as enhanced ROS production, activation of caspase-3/7 and caspase-9, and induction of apoptosis and necrosis in SH-SY5Y cells in a dose- and time-dependent manner. Likewise, the anesthetics mepivacaine and bupivacaine also induced apoptosis in SH-SY5Y cells. Notably, the antioxidantsN -acetyl cysteine (NAC) and Trolox successfully scavenged the mitochondria-derived ROS and suppressed local lidocaine-induced cell death. Conclusions Our findings demonstrate that the local anesthetics lidocaine, mepivacaine, and bupivacaine inhibited the activity of mitochondria and induced apoptosis and necrosis in a dose-dependent manner. Furthermore, they demonstrate that treatment with the antioxidants NAC, Trolox, and GGA resulted in preservation of mitochondrial voltage and inhibition of apoptosis via suppression of caspase activation.